A legal analysis on the distribution and payment of the special pensions under the Special Pensoins Act, 69 of 1969 - Mbedzi, Ndivhuhweni Innocent (My University, 2013)
The South African government has paid compensation in a form of special pension to individuals who have been exposed to certain types of hardship and suffering caused by the governments or their predecessors. This compensation is described as ‘the appreciation or sense of guilty of society towards those people on whom the government has rightfully or wrongfully and at any rate disproportionally inflicted damage’. Government have been prepared to pay compensation to the following persons: former enemies, victims of war, victims of harmful compulsory vaccination measures, persons who had sacrificed their jobs and education in the process of overturning oppressive governments establishing democratic government; and persons whose basic human rights had been violated by governments or their predecessors. These persons have sacrificed their lives either in exile or within South Africa fighting for South Africa to be democratic. These persons must prove that they served their respective political organisations for a period of five years or above or they were banished or restricted in certain area or imprisoned or sentenced.
Thesis (LLM> (Labour Law)) -- University og Limpopo, 2013
Keywords: Pension funds; Pension trusts; Pensions -- Law and legislation -- South Africa; Pension trusts -- Managemet; Social security -- Law and legislation -- South Africa